Aplicaciones de mezclas de biopolímeros y polímeros sintéticos: Revisión bibliográfica - Rodríguez-Sepúlveda, Lady Joana; Orrego-Alzate, Carlos Eduardo (Revista Científica, 2016)
Biopolymers are biodegradable commonly, fragile, hydrophilic and have low thermal resistance, which has limited its commercial application. In contrast, synthetic polymers or derived from non-renewable resources generally lower cost and limited or minimal biodegradability, have good mechanical and thermal characteristics. The blend of biopolymers and synthetic polymers provides materials with properties and reasonable costs for certain applications. This article is a literature review on the main applications recently reported for the most important blends of biopolymers and biodegradable synthetic polymers. The literature search was performed with the "Tree of Science" tool and narratively. The results showed that mixtures of aliphatic and polysaccharide polymers are the most used in engineering applications biological tissues, control drug delivery and packaging industry.